Sexual selection theory meets disease vector control: Testing harmonic convergence as a "good genes" signal in Aedes aegypti mosquitoes. - Garrett P League; Laura C Harrington; Sylvie A Pitcher; Julie K Geyer; Lindsay L Baxter; Julian Montijo; John G Rowland; Lynn M Johnson; Courtney C Murdock; Lauren J Cator (Public Library of Science (PLoS), 2021)
Background The mosquito Aedes aegypti is a medically important, globally distributed vector of the viruses that cause dengue, yellow fever, chikungunya, and Zika. Although reproduction and mate choice are key components of vector population dynamics and control, our understanding of the mechanisms of sexual selection in mosquitoes remains poor. In "good genes" models of sexual selection, females use male cues as an indicator of both mate and offspring genetic quality. Recent studies in Ae. aegypti provide evidence that male wingbeats may signal aspects of offspring quality and performance during mate selection in a process known as harmonic convergence. However, the extent to which harmonic convergence may signal overall inherent quality of mates and their offspring remains unknown. Methodology/principal findings To examine this, we measured the relationship between acoustic signaling and a broad panel of parent and offspring fitness traits in two generations of field-derived Ae. aegypti originating from dengue-endemic field sites in Thailand. Our data show that in this population of mosquitoes, harmonic convergence does not signal male fertility, female fecundity, or male flight performance traits, which despite displaying robust variability in both parents and their offspring were only weakly heritable. Conclusions/significance Together, our findings suggest that vector reproductive control programs should treat harmonic convergence as an indicator of some, but not all aspects of inherent quality, and that sexual selection likely affects Ae. aegypti in a trait-, population-, and environment-dependent manner.